Importancia del aprendizaje de la matematica financiera como herramienta administrativa de la economìa personal en la ciudad de Santa Marta (2021)
The objective of this monographic preliminary project is to determine the learning of financial mathematics as an administrative tool of the personal economy. To this end, the research question is the following: what is the importance of learning financial mathematics as an administrative tool of the personal economy of the city of Santa Marta? In this context, financial mathematics is one of the fundamental pillars to properly manage personal finances.